2013
DOI: 10.1016/j.eats.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Medial Femoral Condylar Coronal Fractures and Nonunions

Abstract: Nonunion of medial femoral condylar coronal fractures are uncommon. In neglected Hoffa fractures despite nonunion, there is a risk of missing accompanying ligamentous and intra-articular injuries. Neither preoperative clinical examination nor magnetic resonance imaging showed these injuries before arthroscopy. Arthroscopy before internal fixation gives additional information and changes the surgical protocol for these fractures and nonunions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Few reports of ARIF of femoral condyle fractures are available. [17][18][19][20][21] Wallenbock and Ledinski 17 in a series of 24 patients of intraarticular knee fractures treated two Hoffa fractures with ARIF. They acknowledge the challenging and demanding nature of work involved in arthroscopic fixation and reported good early results, but they did not describe specifically the technique or outcome of the patients with coronal fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports of ARIF of femoral condyle fractures are available. [17][18][19][20][21] Wallenbock and Ledinski 17 in a series of 24 patients of intraarticular knee fractures treated two Hoffa fractures with ARIF. They acknowledge the challenging and demanding nature of work involved in arthroscopic fixation and reported good early results, but they did not describe specifically the technique or outcome of the patients with coronal fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Although their fixation did not appear to achieve rigid compression, 19 they highlighted reduced soft tissue dissection, blood loss, and operative time and a faster recovery time after arthroscopic management as advantages. Ercin et al 21 described arthroscopy as an important diagnostic tool for management of fixation of these coronal fractures and nonunions. They also advocated that arthroscopy could be considered in all such injuries as associated articular pathologies may be overlooked by clinical or radiological means.…”
Section: Discussionmentioning
confidence: 99%
“…Additional intraarticular injuries such as meniscal tears, chondral lesions, or ACL injuries can be diagnosed and treated as usual, with these arthroscopic techniques. 7 It has been recommended that grafting of the depressed area should be an essential part of the treatment. 8 We prefer a medially based metaphyseal window for lateral tibial plateau fracture because of the advantage of the longer tunnel for better subchondral support as stated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[7,10] The finding of medial or lateral stress test and anterior and posterior drawer test were reported to be positive in some patients. [39,40] Wagih [41] reported that, under general anesthesia, patients with Hoffa fracture have instability at 30° of flexion but not with leg straightened.…”
Section: Diagnosismentioning
confidence: 99%